Angiogenesis as a biomarker and target in cancer chemoprevention. - Sharma, R; Harris, A; Dalgleish, A; Steward, W; O'Byrne, K (2001)
Angiogenesis, the formation of new blood vessels from existing vasculature, is essential to the late stages of carcinogenesis, allowing tumours to grow beyond 1-2 mm in diameter, invade surrounding tissue, and metastasise. However, more than two decades ago, angiogenesis that preceded neoplastic transformation was seen. Indeed, it can be detected in inflammatory and infectious diseases that increase the risk of developing cancer. Recent advances in fluorescence endoscopy and histological assessment suggest that, for certain cancers, the degree of new blood-vessel formation may differ between the early and late stages of carcinogenic progression. The association between angiogenesis and cancer occurrence, and ease of detection of this process in accessible tissues early in carcinogenesis, mean that angiogenesis fulfils the criteria for a biomarker of the effectiveness of chemopreventive intervention. There is also some evidence that biochemical assays of angiogenic growth factors may offer similar potential as surrogate biomarkers. Many natural and synthetic chemopreventive agents in development or in clinical use inhibit new vessel formation in vivo. Validation of angiogenesis as a biomarker for the effectiveness of chemoprevention should further the advancement of some chemopreventive agents.